The myth of generational conflict : the family and state in ageing societies - Arber, Sara, 1949-; Attias-Donfut, Claudine (Routledge/European Sociological Association studies in European societies, 2000)
The ageing of Western societies has provoked extensive sociological debate, surrounding both the role of the state and whether it can afford the cost of an ageing population, and the role of the family, especially women, in supporting older people. In this important book, the authors examine how changes, such as cuts in welfare provision, migration, urbanization and individualisation influence intergenerational relations. The collection addresses theoretical and policy issues connecting age and generation with the family and social policy, and focuses both on cross-cultural compariso.